Fluidized-bed enrichment of marine ammonia-to-nitrite oxidizers and their ability to degrade chloroaliphatics - Melin, Esa S.; Puhakka, Jaakko A.; Strand, Stuart E.; Rockne, Karl J.; Ferguson, John F. (International biodeterioration & biodegradation, 1996)
Ammonia-oxidizing bacteria from marine sediment (Puget Sound, WA) were selectively enriched in a fluidized-bed system (FBS). The enrichment culture converted ammonia stoichiometrically to nitrite. During continuous feed, steady-state ammonia removal was 0.20 mmol/l/h. In a batch fed FBS, at an initial 3.4 mM ammonia concentration, ammonia removal rate was 12 mmol/h/g protein. The enrichment culture degraded cis-1,2-dichloroethene, trichloroethene, methylene chloride and chloroform. Allylthiourea, a specific ammonia monooxygenase inhibitor, prevented degradation suggesting catalysis by nitrifiers. Other compounds, including 1,1,1-trichloroethane, 4-mono-, 2,4,6-trichloro-, 2,3,4,6-tetrachloro-, and pentachlorophenol were not removed. Immunofluorescence assay and polymerase chain reaction (PCR) methods showed that the enrichment culture contained a marine Nitrosomonas species. Extracted DNA from the culture was amplified using 16s rRNA PCR primers designed for the autotrophic ammonium oxidizers of the β-subgroup including marine Nitrosomonas spp., but not with primers designed for Nitrosococcus oceanus. Transmission electron micrographs of the enrichment culture showed bacteria with internal membranes that were similar to those of Nitrosomonas.